1992
DOI: 10.1172/jci115733
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of human tumors with M27 beta, a highly informative polymorphic X chromosomal probe.

Abstract: IntroductionThe clonality of human tumors can be studied by X inactivation/methylation analysis in female patients heterozygous for X-linked DNA polymorphisms. We present a detailed study on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 35 publications
(28 reference statements)
3
54
0
1
Order By: Relevance
“…Recently, Gale et al 29 found significant NRXI in blood-derived cells in 23% of normal females using PGK and HPRT probes and 22% of females using M27␤, 30 which has been confirmed in numerous other studies. [33][34][35][36] Discordance in the incidence of NRXI was initially explained by the diversity of assays used, the different criteria for NRXI, and the small population sizes. However, a more plausible explanation came from studies that analyzed Xinactivation patterns of different tissues in the same female.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gale et al 29 found significant NRXI in blood-derived cells in 23% of normal females using PGK and HPRT probes and 22% of females using M27␤, 30 which has been confirmed in numerous other studies. [33][34][35][36] Discordance in the incidence of NRXI was initially explained by the diversity of assays used, the different criteria for NRXI, and the small population sizes. However, a more plausible explanation came from studies that analyzed Xinactivation patterns of different tissues in the same female.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 99%
“…However, a more plausible explanation came from studies that analyzed Xinactivation patterns of different tissues in the same female. For example, Fey et al 33 reported that the incidence of NRXI was low in gastrointestinal mucosa and thyroid tissue, but was significantly higher in blood cells. Gale et al 31 reported that 45% of females analyzed have different patterns of X-inactivation when blood-derived cells were compared to muscle and skin samples.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 99%
“…For example, assessment of clonality by X-inactivation analysis is based on inactivation of either the paternal or the maternal X-chromosome copy in a given cell and thus represents a marker which preexists in early transformed founder cells of malignant tumours, since X-inactivation patterns in particular cells or tissues are established in early embryogenesis. Therefore, clonal X-inactivation analysis provides insight into an early phase of carcinogenesis and represents an 'early marker' of the clonal relation of different tumour lesions [28]. If a marker captures a 'late' genetic event, it is conceivable that separate tumour lesions in an organ show disparate patterns whilst still being clonally related by virtue of sharing identical X-inactivation patterns.…”
Section: Multiple Tumour Lesions In An Organ: Derived From One or Sevmentioning
confidence: 99%
“…We looked at this problem in a series of gastro-intestinal cancers taken from female patients whereby several geographically distinct tumour areas were examined with a battery of clinically relevant molecular markers [39]. The question of whether these tumours had arisen from one or perhaps a few single mucosal founder cells was tackled by clonal X-inactivation analysis [28]. Each tumour (with one exception) showed a uniform clonal X-inactivation pattern throughout all of the samples, suggesting the cancer's origin in a single early mucosal founder cell.…”
Section: Multiple Tumour Lesions In An Organ: Derived From One or Sevmentioning
confidence: 99%
“…Activation by RAS of the RAL guanine nucleotide exchange factor is responsible for dampening the G 2 arrest induced by ethyl methanesulfonate in p53-deficient MDAH041 fibroblasts (24). On the other hand, activation of the RAS downstream effectors MEK2 3 and ERK are required for exit from DNA damage-induced G 2 cell cycle arrest (25) and the transition from G 2 into M (26,27), respectively.…”
mentioning
confidence: 99%